THE IMPACT OF RISK MANAGEMENT ON THE PERFORMANCE OF CONSTRUCTION PROJECTS - Mofleh Alshehhi, Hamad Saleh (PEOPLE: International Journal of Social Sciences, 2024)
This study delves into the integral role of risk management in optimizing the efficiency of construction project implementation by identifying and categorizing potential risks while emphasizing proactive risk management strategies. The research underscores the vulnerability of construction projects to diverse risks and highlights the prevailing issue of insufficient emphasis on risk management practices in the field. Notably, the findings indicate a substantial correlation between early risk identification and heightened project efficiency, showcasing that project employing proactive strategies experience fewer disruptions and greater adaptability to unforeseen challenges. Furthermore, construction projects implementing robust risk management practices demonstrate noteworthy reductions in delays and cost overruns, contributing to streamlined timelines and adherence to budget constraints. The study recommends prioritizing the adoption of proactive risk management practices, focusing on early identification and mitigation, and advocates for investment in training programs to enhance stakeholders’ risk management knowledge and skills. Additionally, it suggests leveraging technological solutions, such as predictive analytics and simulation models, for more accurate and dynamic risk assessments, facilitating informed decision-making in construction project management. The comparative analysis of risk management approaches empowers informed and appropriate decision-making. This reduces the disruption of and enhances financial outcomes. These findings signify a paradigm shift in project management in construction, advocating for a culture of effective and proactive risk management. It can revolutionize industry practices, increase predictability, and elevate the project’s success. Implementing recommended strategies, inculcating adaptability cultivation, clear communication, and theoretical framework, and embracing complexity promises to enhance risk management effectively, guiding the instruction industry toward continuous improvement and innovation.